(In)visibilization of English learners in Minnesota's state-approved alternative programs. Issue 1 (15th March 2021) - Schornack, Miranda Lee; Karlsson, A.
ABSTRACT: Speakers of languages other than English are positioned as problems within education systems and 'low' academic English proficiency is viewed as something to be fixed. Alternative education programs are typically viewed as punitive, substandard, exclusionary academic settings. Therefore, speakers of languages other than English (ELs) enrolled in alternative education programs face what we refer to as hybrid imagery challenges. This paper examines enrollment of ELs in Minnesota's State Approved Alternative Programs (SAAPs), highlighting the hybrid imagery challenges in language policy and planning (LPP). We juxtapose principal (building administrator) beliefs about low EL enrollment with state-level enrollment reports, to reveal the impacts of unplanned language planning at the state-level and theorize how various actors enact agency in ways that (in)visibilize ELs enrolled in Minnesota's SAAPs. We identify the monoglossic language ideological stance that pervades a state committed to improving the educational conditions for ELs. We call for immediate action in three areas: (1) research that examines why ELs are disproportionately enrolled in alternative education programs; (2) education policies that assume a heteroglossic stance, viewing language development as lifelong; and (3) approaches that disrupt linguistically inequitable school practices every day, especially those that one has contributed to themselves.